Effects of long-term mineral fertilization and manuring on rice-rice cropping pattern in sub-tropical floodplain soil - Mostofa, Bornali; Raihan, Md Zahir; Hossain, Mohammad Forhad; Farhana, Taneya; Mia, Md Mukul; Kader, Md Abdul (Asian Journal of Medical and Biological Research, 2015)
An experiment was carried out both boro season (FebruaryJune, 2013) and aman season (July-December, 2013) in the permanent experimental field of the Department of Soil Science, Bangladesh Agricultural University (BAU), Mymensingh. The objectives of present research work were tosee the effects of long-term fertilization and manuring on soil fertility and yield of boro and aman rice in flood plain (Subtropical) soil (AericHaplaquepts). The experiment was laid out in a randomized complete block design with three replications. There were 10 treatment combinations viz, Control, N, NP, NK, NPK, NZn, NS, NSZn, NPKSZn and NPK+FYM. The results indicated that the yield contributing characters and yield of BRRI dhan28 (Boro rice) and BR11 (Aman rice) were significantly increased due to different treatments. For boro rice, the highest plant height (cm), 1000-grain weight (g), effective tiller hill-1 and biological yield (t ha-1) were found in NPKSZn treatment. The highest grain yield and straw yield of boro ricewere also observed in NPKSZn treatment. Grain yield was increased by 71%, 119%, 127%, 132%, 133%, 144%, 161% and 200% over Control in NZn, NS, NK, N, NP, NPK+FYM, NPK, NSZn and NPKSZn treatments, respectively. Straw yield was increased by 82%, 83%, 98%, 110%, 112%, 139%, 145%, and 167% over Control in N, NP, NPK+FYM, NZn, NK, NPK, NSZn, NS and NPKSZn treatments, respectively. Again for aman rice, the highest number of unfilled grain panicle-1, grain yield (t ha-1) and harvest index (%) were recorded in NPKSZn treatment. Grain yield was increased by 79%, 85%, 87%, 97%, 116%, 117%, 159% and 165% over Control in NP, NZn, N, NPK, NPK+FYM, NK, NSZn, NS and NPKSZn treatments, respectively. Straw yield was increased by 119%, 121%, 135%, 142%, 149%, 152%, 200%, 217%, and 246% over Control in NP, N, NPK, NPK+FYM, NK, NZn, NPKSZn, NSZn and NS treatments, respectively. Asian J. Med. Biol. Res. June 2015, 1(2): 222-229